2015
DOI: 10.17096/jiufd.73461
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Extraoral Cutaneous Sinus Tracts With Non-Surgical Endodontic Intervention: Report of Six Cases

Abstract: Clinically, extraoral sinus tracts of endodontic origin may be confused with a wide variety of diseases. Thus, the differential diagnosis of this clinical dilemma is of paramount importance in providing appropriate clinical care because misdiagnosis of this condition may result in healing failure or unnecessary treatments. For this reason, a dental cause must be considered for any cutaneous sinus tract involving the face or neck. Its diagnosis is not always easy unless the treating clinician considers the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This preventive approach is little described in the literature. Both of these methods have been tested by McCLUER from 1961 with similar aesthetic results [14,15].…”
Section: Unsightly Scarsmentioning
confidence: 99%
“…This preventive approach is little described in the literature. Both of these methods have been tested by McCLUER from 1961 with similar aesthetic results [14,15].…”
Section: Unsightly Scarsmentioning
confidence: 99%
“…[17,18] Once the correct diagnosis is made, definitive treatment, through either tooth extraction or root canal therapy to eliminate the source of infection, is simple and effective. [19] In this case report, the diagnosis and treatment of an odontogenic extraoral sinus tract are described.…”
Section: Introductionmentioning
confidence: 98%
“…It may cause unnecessary treatment such as surgical interventions and long-term antibiotic treatment before the correct diagnosis can be made. [4][5][6][7][8] Since there are no dental symptoms, patients first refer to dermatologists for the treatment of lesions. However, extraoral sinus tracts seen in the head and neck region usually develop due to endodontic infections.…”
mentioning
confidence: 99%
“…In order to resolve periapical pathology in non-surgical endodontic treatment, it is necessary to remove the infected material in the root canals and the root canals must be sealed three dimensionally. 6,8,12 Akpınar et al reported that 80.4% of the teeth in the odontogenic sinus tract were treated with only root canal treatment, 12.8% were treated with root canal treatment and endodontic surgery and the remaining 6.8% were treated with tooth extraction. 11 Unfamiliar objects in root canals are often seen in children and usually detected by chance.…”
mentioning
confidence: 99%